The Role of Human Resource Management in Improving Organizational Performance - Patswawati, Patswawati; Arifin, Antoni Ludfi (Dinasti Publisher, 2025)
The implementation of human resource management strategies is useful for evaluating how well employees perform their jobs and their competence in the field. Apart from that, there is an increase in employee performance due to system changes as well as motivation, targets, compensation and rewards. The objective of this research is to explore how human resource management strategies improve employee performance. The research results show that in the realm of business and management, the role of human resource management (HR) in improving organizational performance is very important. This type of research is qualitative research, with collection tools. The data uses observation, interviews and documentation methods. This research is characterized as descriptive qualitative, in its data analysis techniques using data reduction, data display, and conclusion drawing or verification, by analyzing several HR journals and reference books, it produces evidence that Human Resource Management is recognized as a vital element for improving organizational performance. Resource Management is seen as a strategic resource that can give a company a competitive advantage in the long term. The main goal of Resource Management management is to provide a workforce that is productive and successful in achieving the company's strategic goals.